A Systematic Literature Review on the Use of Gamification in English Language Teaching for Young Learners - Lena Amalia; Faza Amelia (Research Synergy Foundation, 2025)
Gamification has become a popular strategy in education for increasing student motivation and engagement. In English Language Teaching (ELT) for young learners aged 5 to 12, gamification is especially important because children in this age group learn better through play, interaction, and fun activities than through memorization. However, there is still limited understanding of how gamification specifically supports young learners’ English learning. This study presents a systematic literature review (SLR) on the use of gamification in ELT for young learners. This study focuses on the intersection between two key variables—gamification and English instruction for children—and explains why their combination is meaningful. Gamification can address common learning challenges such as short attention spans and low motivation by creating interactive, engaging, and developmentally appropriate learning environments. This review followed the PRISMA 2020 guidelines and used the Scopus database to collect articles published between 2016 and 2025. Of the 75 identified articles, 14 studies met the inclusion criteria and were analyzed. Results showed that gamification enhances student motivation, improves grammar acquisition through tools like Kahoot! and Quizizz, and supports engagement in hybrid learning settings. A key limitation of this review is its narrow focus on grammar, as most studies did not explore other essential language skills such as listening, speaking, reading, and writing. Future research should examine how gamification can support a broader range of skills. This review offers practical insights for educators and researchers by highlighting how gamification can be applied thoughtfully to enhance English learning for young learners.